Adsorption of Cu (II) on the Surface of Nonconventional Biomass: A Study on Forced Convective Mass Transfer in Packed Bed Column. (7th March 2013) - Mishra, Vishal; Balomajumder, Chandrajit; Agarwal, Vijay Kumar
Abstract : The present investigation has dealt with the adsorption of Cu (II) across liquid phase on the nonconventional adsorbent. The nonconventional adsorbent used in the present work was Cedrus deodara sawdust obtained from local carpenter's shop. The maximum uptake capacities of Copper (II) ions at saturation and breakthrough point were 55.63 mg/g and 53.18 mg/g for an initial concentration of 93 mg/L of copper, respectively. The fitting of the experimental data in Langmuir, Freundlich, and Temkin isotherm models indicated the suitability of Langmuir isotherm in terms of very low statistical error functions that is, χ 2 and sum of square errors (SSE) and higher values of ( R 2 ) linear regression coefficient. The goodness of fit of the breakthrough curve in Bohardt-Adams, Wolborska, Modified dose response, and Thomas model indicated the suitability of Thomas model with higher linear regression coefficient and lower values of statistical error functions. The flow rate and bed height affected the hydrodynamic parameters of the packed bed reactor significantly.